The transcriptomic fingerprint of cancer response to Tumor Treating Fields (TTFields) - Kerem Wainer-Katsir; Adi Haber; Hila Fishman; Lianghao Ding; Michael D. Story; Renfei Du; Ulf D. Kahlert; Laura Mannarino; Federica Mirimao; Monica Lupi; Maurizio D’Incalci; Gitit Lavy-Shahaf; et al. (Cell Death Discovery)
Abstract Tumor Treating Fields (TTFields) therapy is an approved cancer treatment modality, based on non-invasive application of electric fields to the tumor region. Proteomic and cell biology methods revealed a versatile mechanism of action to be involved in the response to TTFields. In the current research we performed whole transcriptome analysis across tumor types to identify pan-cancer responses to TTFields. For this we collected samples from control and TTFields-treated human cancer cell lines of gastric cancer, pancreatic cancer, ovarian cancer, non-small cell lung carcinoma, pleural mesothelioma, and glioblastoma. The transcriptomic analysis supported previous reported effects: downregulation of pathways associated with cell cycle, cell growth, and proliferation; downregulation of DNA replication and the FA-BRCA DNA repair pathway; and upregulation of cellular responses to stress—senescence, autophagy, and apoptosis. Notably, previously unrecognized downstream effects of TTFields were revealed on cellular metabolism, with downregulation of protein and RNA metabolism, and upregulation of steroid biosynthesis. Additional DNA repair pathways were also found to be downregulated, including nucleotide excision repair, base excision repair, and mismatch repair. In conclusion, this study revealed similar response patterns to TTFields across different tumor types, re-enforcing some already pinpointed mechanisms, while revealing new mechanisms. Unlocking these new mechanisms may allow identification of potential new cancer treatments for application together with TTFields based on mechanistical compatibility.